Monopulse sum and difference signals with compensation for a failed feed element. Issue 6 (1st April 2016) - Sheret, Tamara Louise; Allen, Ben; Parini, Clive G.
Abstract : Monopulse antenna systems are commonly used in airborne radar as they give angular information in a single measurement. For amplitude based monopulse antenna systems, multiple overlapping beams are sent out from the antenna feed elements. These signals may then be re‐combined using a comparator network to form the sum and difference signals, which provide angular information relating to the target position. This study investigates a proposed method by which the individual feed element signals from the monopulse antenna are captured and combined in software, thus removing the need for a hardware comparator behind the feed elements. Results of a sum and difference signal created by a comparator and by this proposed method are compared. This study then verifies a method by which the individual feed element signals from the monopulse antenna are captured, combined in software and presents a novel method to compensate for a failed feed element signal, verified in both simulation and anechoic chamber measurements. It is shown that this new compensation for a single failed feed element works well for a signal in the centre of the monopulse antenna, where gain and sum patterns are shown to be conserved.